Recovery of Indigenous community practices. Notes for a decolonial pedagogy within the framework of the New Mexican School - Cruz Hernández, Jorge Luis; Corral Monroy, María Maydelid; Bravo Moreno, Josefa (IE Revista de Investigación Educativa de la REDIECH, 2024)
This research is based on the proposals of international and national organizations, which expose the need for a new educational discourse for the future of humanity and the planet. In the case of Mexico, with the so-called New Mexican School (NEM) a scenario of possibility is glimpsed, whose Indigenous community knowledge and practices are the focus of attention. However, the present of these people is determined by external factors that influence the loss of community knowledge, therefore, the objective of this work is to find out the causes of this loss in order to recover them through decolonial pedagogy. A quantitative methodology was used through the explanatory method of causality. Surveys were applied to the population of the Otomi communities surrounding the National Pedagogical University 151, Toluca, at its Acambay Regional Headquarters. Some results show that the loss of beliefs and the disuse of the mother tongue are the causes of the disintegration of the sense of community. It is concluded that educational institutions must start from the inclusion of spiritual practices and the resignification of subjectivities for the construction of a decolonizing pedagogy within the framework of the NEM.